ICU nutrition in the UK : How we do it? - Divekar, Nandita (Indonesian Nutrition Association, 2025)
Optimal nutritional support has a fundamental role in the management of critically ill patients. It has a significant impact on morbidity, mortality and patient outcomes. In the United Kingdom nutritional protocols are in alignment with the National and International guidelines for nutrition.